A study on performance characteristics of vapor injection heat pump cycle with indirect heat recovery. (1st September 2022) - Wei, Yuan; Liu, Shuilong; Yu, Jianlin
Highlights: An indirect heat recovery of fresh air system is proposed. A sub-cooler and an evaporator are added at the conventional vapor injection heat pump cycle. The volumetric heating capacity and coefficient of performance are improved significantly. The novel cycle has excellent potential for performance improvement in heat pump equipment. Abstract: This paper proposes a vapor injection heat pump cycle with indirect heat recovery, which adds a sub-cooler and an evaporator on the basis of conventional vapor injection heat pump cycle. In the added first sub-cooler, refrigerant exchanges heat with outdoor fresh air entrancing into indoor for improving the indoor air quality, which increases the temperature of the outdoor fresh air and the subcooling of refrigerant. In the added high-temperature evaporator, refrigerant absorbs the heat from indoor exhaust air through heat exchange, which can improve the heating capacity and the cycle performance. The refrigerant R32 is selected as the working fluid to analyze the performance of the cycle. The results show that under the same operating conditions, the volumetric heating capacity of the cycle is increased by 33%–72% and the coefficient of performance is improved by 20.5%–33.5% compared with the conventional sub-cooler vapor injection heat pump cycle. When the outdoor ambient temperature is lower, the improvement ratios of volumetric heating capacity and coefficient of performance is larger. Therefore, this novel cycle is suitable to be used at the lower ambient temperatures. In addition, the larger fresh air ratio can bring better cycle performance.